2008
DOI: 10.1063/1.2963975
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube screening effects on the water-ion channels

Abstract: A self-consistent tight-binding method is used to investigate the screening effects of semiconducting and metallic single-wall carbon nanotubes ͑SWCNTs͒ when the water molecules and various charged ions pass through the nanotubes. The trajectories of ions and water molecules are obtained from molecular dynamics simulations. It is shown that metallic SWCNTs have much stronger screening abilities than semiconducting SWCNTs. Our results indicate that it is possible to distinctly identify different ions and also t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Xu and Aluru (2008) investigated the screening effects of semiconducting and metallic single-walled CNTs (SWCNTs) when the water molecules and various charged ions pass through the nanotubes. It is shown that metallic SWCNTs have much stronger screening abilities than semiconducting SWCNTs.…”
Section: Particle Separation or Screeningmentioning
confidence: 99%
“…Xu and Aluru (2008) investigated the screening effects of semiconducting and metallic single-walled CNTs (SWCNTs) when the water molecules and various charged ions pass through the nanotubes. It is shown that metallic SWCNTs have much stronger screening abilities than semiconducting SWCNTs.…”
Section: Particle Separation or Screeningmentioning
confidence: 99%
“…Furthermore, Tet treatment resulted in a significant increase in RGC survival in vivo, with transient elevation of IOP, 1 day after I/R. The protective effects of Tet could involve multiple pharmacologic actions such as blocking the calcium influx, 3 , 4 inhibiting lipid peroxidation, 5 reducing the generation of ROS, 6 suppressing the production of cytokines and inflammatory mediators, and reducing neuronal apoptosis. 9 , 47 …”
Section: Discussionmentioning
confidence: 99%
“…Tetrandrine (Tet) is a bisbenzylisoquinoline alkaloid extracted from the root of the Chinese herb creeper Stephania tetrandra . 1 , 2 It is a calcium channel blocker 3 , 4 that inhibits lipid peroxidation 5 and the generation of reactive oxygen species (ROS) 6 and suppresses the production of cytokines and inflammatory mediators in the brain after ischemia reperfusion injury, 6 , 7 anoxia, 8 or Alzheimer’s disease. 9 Tet ameliorates amyloid-β(1–42)-induced spatial learning and memory impairment, and the beneficial effect of tetrandrine treatment may be linked to the inhibition of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) activity and downregulation of interleukin-1β and tumor necrosis factor-α.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] The possibility to detect and identify different charged ions translocating through CNTs has recently been reported. 14 Since DNA bases with backbones are negatively charged, the confinement of DNA inside CNT makes the detection of electrostatic signals generated by DNA bases possible. Furthermore, abnormal and normal DNA segments have different charge distribution, so it is also possible to differentiate them by measuring the electrical signals.…”
mentioning
confidence: 99%
“…The screening ef-fects are computed by self-consistent tight-binding ͑TB͒ simulations. 15 Since semiconducting CNTs have much weaker screening ability than metallic CNTs, 14 we use semiconducting CNTs to obtain stronger electrical signals when DNA bases are present inside the CNT. The TIP3P model is used for the geometry and atomic charges of water molecules.…”
mentioning
confidence: 99%